One-Pot Multi-Reaction Processes: Synthesis of Natural Products and Drug-Like Scaffolds - Calder, Ewen D. D.; Grafton, Mark W.; Sutherland, Andrew (Synlett, 2014)
One-pot multi-reaction processes involving Overman rearrangements, metathesis cyclizations, and Diels–Alder reactions have been developed for the rapid and efficient synthesis of amino-substituted carbocyclic and heterocyclic compounds. This account describes the development and optimization of these processes, as well as their applications in the synthesis of natural products and drug-like scaffolds.1 Introduction2 A One-Pot Overman Rearrangement and Ring-Closing Metathesis Reaction2.1 Scope and Limitations2.2 Applications of the One-Pot Two-Step Process2.3 A Directed Overman Rearrangement and Ring-Closing Metathesis Reaction Process3 A One-Pot Three-Step Ruthenium(II) Tandem Catalytic Process3.1 Development and Scope3.2 A Microwave-Mediated One-Pot Three-Step Process4 A One-Pot Three-Step Process Involving a Ring-Closing Enyne Metathesis and a Diels–Alder Reaction4.1 Synthesis of Substrates4.2 An Unexpected Hydrogen-Bonding-Directed Diels–Alder Reaction4.3 Application of the Synthesis for C1-Amino-Substituted Indanes and Tetralins4.4 Development of a Two-Pot Reaction Process5 Conclusions
Keywords: Overman rearrangement; metathesis; Diels–Alder reaction; catalysis; transition metals; multistep reaction